Impact of Psychological Capital on Employees’ Job Performance: An Empirical Study on Private Banks Employees in Badulla District - Thennakoon, T.M.I.G.; Renusha, M. (University of Vavuniya, 2022)
The study primarily focused on the impact of Psychological Capital on Employees’ Job Performance in private banks. For this, Badulla District has been selected. The population of the study consists of every level of employees working in the above-mentioned private banks. The sample consists of 150 employees who were selected using convenient sampling. Data was collected through the self administered and structured questionnaire. The present study empirically evaluates four dimensions of Psychological Capital: Hope, Resiliency, Optimism and Self-Efficacy. The study suggests that these variables significantly impact the Employees’ Job Performance. Finally, through this study, the authors conclude that Psychological capital significantly impacts the employees’ job performance. Thus, the organization’s administration can use Psychological Capital to improve their employees' job performance.
Keywords: Psychological Capital; Hope; Resilience; Optimism; Self-Efficacy; Employees’ Job Performance